2002
DOI: 10.1038/sj.bdj.4801609
|View full text |Cite
|
Sign up to set email alerts
|

The tunnel restoration

Abstract: The aims of this paper are to give a brief history of the tunnel restoration, to describe and illustrate one way of making this restoration and to review the clinical trials of the procedure carried out to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The authors view this dropout rate as normal, compared to dental clinical studies of the same duration. 34 In other studies, subjects dropping out of clinical trials typically have worse dental outcomes than those who remain. In the current study, subjects were more likely to return if they had problems, since the authors of the current study promised to replace the restorations at no charge.…”
Section: Discussionmentioning
confidence: 99%
“…The authors view this dropout rate as normal, compared to dental clinical studies of the same duration. 34 In other studies, subjects dropping out of clinical trials typically have worse dental outcomes than those who remain. In the current study, subjects were more likely to return if they had problems, since the authors of the current study promised to replace the restorations at no charge.…”
Section: Discussionmentioning
confidence: 99%
“…Strand et al18 reported a higher failure rate of glass ionomer tunnel restorations in patients with high caries activity. This is also suggested by Ratledge et al4 who found that people with high caries activity had high risk of secondary caries 4. This may be due to the design of tunnel preparation, which does not clear the proximal contact, and the restorative margin in the proximal contact is subjected to cariogenic challenge by the plaque sheltered below the contact point.…”
Section: Literature Reviewmentioning
confidence: 75%
“…The tunnel preparation was first reported in the 1960s for restoring distal proximal caries of a primary second molar, accessing caries beneath the marginal ridge and thus leaving it intact 4. In the 1980s, tunnel preparation was reintroduced with the use of glass ionomer cement 5,6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The slot prep was compared and found to be a more reliable alternative. 20 When an amalgam is placed the matrix band is removed before the material setting and the restoration springs back and establishes a good contact. Unfortunately resin composite is set before the band removal and often leaves a gap between the new restoration and the adjacent tooth.…”
Section: Discussionmentioning
confidence: 99%